2014
DOI: 10.1155/2014/216964
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Total Serum Antioxidant Capacity in Healthy Men and in Men with Coronary Heart Disease

Abstract: Whether the incidence of coronary heart disease (CHD) is related to a decrease in total antioxidant capacity (TAC) has not yet been completely clarified. We assessed TAC of blood serum in a group of 163 men with CHD aged 34.8–77.0 years and in 163 age-matched peers without CHD. Two spectrophotometric methods were applied to assess TAC: ferric reducing ability of serum (TAC-FRAS) and 2.2-diphenyl-1-picryl-hydrazyl (TAC-DPPH) tests. In the CHD group, multivariate analysis revealed that uric acid (UA), triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…In fact, the sulfhydryl groups in Hcy were oxidized to disulfide, catalyzed by the transition metals which product several OFR (hydroperoxides: H 2 O 2 ), and initiates lipid peroxidation responsible of endothelial injury 11,28 . Erythrocyte SOD activity was significantly decreased in IHD cases wich is in agreement with several studies such as those reported by Almzaiel AJT et al 14,29,30 . SOD, FR scavenging enzyme, are the first line of cellular defense against oxidative injury 20 .…”
Section: Fig 2: Negative Correlations Among Ihd Patients (Hs_crp-tassupporting
confidence: 92%
“…In fact, the sulfhydryl groups in Hcy were oxidized to disulfide, catalyzed by the transition metals which product several OFR (hydroperoxides: H 2 O 2 ), and initiates lipid peroxidation responsible of endothelial injury 11,28 . Erythrocyte SOD activity was significantly decreased in IHD cases wich is in agreement with several studies such as those reported by Almzaiel AJT et al 14,29,30 . SOD, FR scavenging enzyme, are the first line of cellular defense against oxidative injury 20 .…”
Section: Fig 2: Negative Correlations Among Ihd Patients (Hs_crp-tassupporting
confidence: 92%
“…Plasma TAC measurements were performed using two spectrophotometric methods: FRAP [8] with some modifications [12], and the DPPH test [12,14]. The details of both methods are described elsewhere [12,16]. Both tests were executed with native plasma samples (containing UA) and pretreated with uricase and catalase (with decomposed UA), as described elsewhere [15].…”
Section: Plasma Tac and Nu-tacmentioning
confidence: 99%
“…Uric acid is a major antioxidant in serum . The level of antioxidant activity in each experimental group was evaluated by measuring the serum uric acid level.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the serum cytokine profile, the change in the antioxidant capacity of plasma is related to MetS . Many serum molecules contribute to the serum antioxidant activity, and uric acid is one of the major antioxidants of serum antioxidant activity with MetS .…”
Section: Discussionmentioning
confidence: 99%